Latent heat validation of phase change material using t-history method - Mohd Rosli, Mohd Afzanizam; Chia, Zhi Horng; Ponnaiyan, Jayaprakash; Salimen, Nurfarhana; Herawan, Safarudin Gazali; Hussain, Faridah; Abdul Rashid, Azrin Hani (Penerbit Akademia Baru, 2025)
Phase change material (PCM) is a material that will absorb and release heat over a specified timeframe and it functions as a cooling technique to reduce temperature of the photovoltaic panels. The T-history method is a technique used to measure the thermal diffusivity of a material by subjecting a sample to a sudden temperature change. This project proposed PCM36 as a cooling method for PV temperature reduction and the expected result for this study is to meet the data from manufacturer with a small different percentage. T-history is introduced to validate the PCM36 latent heat capacity and melting point and thus compare it with the manufacturer data. The manufacturer data's latent heat capacity and melting point are 220 J/g and 36 ˚C, respectively. Based on the result obtained, the latent heat capacity from T-history is 217.891 J/g and is 0.9591% different compared with the manufacturer data. On the other hand, the melting point based on the T-history curve is in the range of 36 ˚C-38 ˚C, which is similar to the manufacturer data.